Little negligence leading to irreparable harm: thinner burns - Kemal Arslan; Arif Atay; Tamer Sekmenli; Metin Gunduz; Osman Dogru; Ilhan Ciftci (Medicine Science, 2017)
The aim of the present study is to evaluate the epidemiology and outcome of paint thinner induced burn injuries at a local burn center. A retrospective analysis of 55 patient paint thinner thermal burn cases was conducted. Relevant patients data such as age, sex, etiologic factors, burn extent and localization, employed methods of treatment, hospitalization period, and results were evaluated in retrospect from patients records. 50 male and five female patients with a mean age of 26,78 (14-47) years participated in the presented study. Kindling fire with paint thinner was the most frequent etiologic factor. Total body surface burn area was 22,5 % (5-90). The mean hospitalization period of the survivors was 24 (5-64) days. Early excision and split-thickness sking grafting was applied in 22 patients. The remaining 26 patients were treated with topical agents. Total mortality was only 7 (12.7%). These patients had paint thinner induced burned body surfaces of 60 % with accompanying inhalation injuries. Paint thinner may cause catastrophic thermal injuries even with terminal outcomes and should therefore never used to kindle a fire. [Med-Science 2017; 6(4.000): 733-736]